2006
DOI: 10.1016/j.cell.2005.10.032
|View full text |Cite
|
Sign up to set email alerts
|

The Processivity of Multiubiquitination by the APC Determines the Order of Substrate Degradation

Abstract: The anaphase-promoting complex (APC) coordinates mitosis and G1 by sequentially promoting the degradation of key cell-cycle regulators. Following the degradation of its substrates in G1, the APC catalyzes the autoubiquitination of its E2 UbcH10. This stabilizes cyclin A and allows it to inactivate APC(Cdh1). How the APC establishes this complex temporal sequence of ubiquitinations, referred to as substrate ordering, is not understood. Here we show that substrate ordering depends on the relative processivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
269
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(279 citation statements)
references
References 27 publications
7
269
1
2
Order By: Relevance
“…The function of the UBE2C gene product is closely linked to cell cycle progression and the destruction of mitotic cyclins. Rape et al 32,34 showed that the decision between cyclin A degradation and anaphase-promoting complex inactivation is determined by UBE2C availability. Our study demonstrated that siRNA-mediated suppression of UBE2C expression inhibited the growth rate of CRC cells with accumulation of cyclins A and B1, which was consistent with earlier reports.…”
Section: Discussionmentioning
confidence: 99%
“…The function of the UBE2C gene product is closely linked to cell cycle progression and the destruction of mitotic cyclins. Rape et al 32,34 showed that the decision between cyclin A degradation and anaphase-promoting complex inactivation is determined by UBE2C availability. Our study demonstrated that siRNA-mediated suppression of UBE2C expression inhibited the growth rate of CRC cells with accumulation of cyclins A and B1, which was consistent with earlier reports.…”
Section: Discussionmentioning
confidence: 99%
“…The length of the polyubiquitin chains affects degradation [19]. For example, the E3 anaphasepromoting complex (APC) coordinates the order of substrate degradation during the cell cycle and the timing by which substrates are degraded depends on the processivity of their ubiquitination by APC [19].…”
Section: Substrate Targeting To Proteasesmentioning
confidence: 99%
“…For example, the E3 anaphasepromoting complex (APC) coordinates the order of substrate degradation during the cell cycle and the timing by which substrates are degraded depends on the processivity of their ubiquitination by APC [19]. Substrates that acquire long ubiquitination chains quickly are degraded earlier than substrates that are ubiquitinated slowly [19].…”
Section: Substrate Targeting To Proteasesmentioning
confidence: 99%
“…7), and ubiquitination assays were performed as described previously (Rape et al 2006). Briefly, 0.05 mg/mL recombinant PR-Set7 was incubated with 30 nM purified APC cdh1 , 0.05 mM E1, 1 mM E2 (UBCH10), and 1 mg/mL ubiquitin for 30 min and 60 min prior to Western analysis.…”
Section: Apc Ubiquitination and Degradation Assaysmentioning
confidence: 99%